Sesame Street sign language fun - Bove, Linda; Cooke, Tom; National Theatre of the Deaf. (New York : Random House/Children's Television Workshop, 1980)
Presents in sign language words grouped in such categories as the family, school, color, playground, seasons, utensils and food, woods, transportation, jungle, and feelings and emotions.
Keywords: American Sign Language -- Juvenile literature; Sign language